Technical efficiency analysis: Management factor as determinants of saving and credit cooperatives’ health - Atik Purmiyati, - (Elsevier Ltd., 2022)
The main purpose of this study is to analyze the technical efficiency of Saving and Credit Cooperatives (SACCOs) and the impact for SACCOs’ health using primary data obtained from a survey of 178 respondents of SACCOs in East Java, Indonesia. The three stages of the analysis used are Data Envelopment Analysis (DEA), Tobit Regression and Logistic Regression. Based on the results of the analysis using the DEA method, it is concluded that the average performance that can be achieved by SACCOs with existing technology is 65 % of the maximum potential yield. There are 61.3 % of SACCOs which are declared technically inefficient. The factors that influence the level of technical efficiency of Saving and Credit Cooperatives are interest, loan term, manager's age, and type of business. Furthermore, the factors that affect the health of the cooperative based on logistics analysis are the variable frequency of management meetings, age of the cooperative, fixed deposits and average loan. This study supports the SACCOs in becoming more efficient and healthy with the influence of external policy (from government) and internal policy (from SACCOs).